FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK SAFETY DRIVING PADA PENGEMUDI MOBIL SKID TANK DI PT X - Zulkarnaen Zulkarnaen; Daru Lestantyo; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Safety driving is the right way to drive, knowing the right driving techniques, understanding and following the traffic rules so that driving will always be safe and can help to avoid traffic problems.During the year 2016-2017 there have been 2 skid tank car accident owned by PT X on the way. The purpose of this study is to analyze the relationship between age, employment, knowledge, attitude, safety briefing, participation of safety driving training, the role of supervisor and the role of partner. This research uses quantitative research with cross sectional approach. The population of this study is all skid tank car drivers in PT X which amounted to 38 people with a total sample of 38 people. Sampling method was done by total sampling technique.The independent variables in this research are age, working period, knowledge, attitude, safety briefing, participation of safety driving training, role of supervisor and role of co-worker. and the dependent variable of safety driving practices. The result of research is 60,5% of respondent have good driving safety practice. Based on Chi-Square statistic test, the variables related to safety driving practice are knowledge (p-value: 0,033), attitude (p-value: 0,041), safety briefing (p-value: 0,024), participation of safety driving training (p- value: 0.006), and the role of supervisor (p-value: 0,024). While the unrelated variables are age (p-value: 0.775), tenure (p-value: 1,000), and the role of co-workers (p-value: 0.286). The researcher advises the driver to follow and implement the company's policy regarding safety aspects that start from the beginning before doing the job and for the company to provide training to all drivers as well as to make a list of materials and schedule of filler safety briefing activities.